EFFECT OF WATER LEVEL ON MIGRATORY BIRDS HABITAT AT LAKE MAGGIORE - C. Tattoni; S. Giuntini; A. Gagliardi; A. Martinoli; R. Lardelli; N. Patocchi; A. Martinoli; D. G. Preatoni (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Migratory birds need to stop along their route to rest and feed at so called stopover sites. “Bolle di Magadino” is a protected wetland located near lake Maggiore (CH), an internationally recognized nesting and stop-over site for birds. The waters of Lake Maggiore are important resources for multiple usages, and are artificially regulated through a dam. Even slight variations in the water level are sufficient to cause flooding and draining of large portions of the wetlands, affecting foraging and resting opportunities for birds. We use open data and FOSS4G to study the effect of water level on bird migration. We compared the extent and type of flooded habitat using two approaches: Sentinel-1 remote sensing imagery and simulations based on the measured water level. The effect of type and extent of submerged vegetation obtained with both methods was tested against a time series of bird captures. Both methods had a similar temporal pattern of flooding in autumn, but nearly opposite in spring. The total extent and the type of submerged habitats showed significant differences. The results obtained by simulations based on water level were more correlated to birds captures and species richness than the estimations of flooded habitat derived by with Sentinel-1. The results presented here will contribute to the definition sustainable management tools of water management of lake Maggiore taking into account the effect of lake level on biodiversity.